Glutamine Supplementation Enhances the Effects of a Low FODMAP Diet in Irritable Bowel Syndrome Management - Rastgoo, Samira; Ebrahimi-Daryani, Nasser; Agah, Shahram; Karimi, Sara; Taher, Mohammad; Rashidkhani, Bahram; Hejazi, Ehsan; Mohseni, Fatemeh; Ahmadzadeh, Mina; Sadeghi, Amir; Hekmatdoost, Azita (Frontiers in Nutrition, 2021)
Background and Aims: Although irritable bowel syndrome is one of the most common gastrointestinal disorders presented to gastroenterologists, therapeutic strategies are not yet well-established. Accordingly, we conducted a randomized, double-blind, placebo-controlled, clinical trial to evaluate the possible superiority of adding glutamine supplement to low fermentable oligo- di- monosaccharides and polyols (FODMAP) diet in patients with irritable bowel syndrome (IBS). Methods: Eligible adults were randomized to receive a low FODMAP diet either with glutamine (15 g/day) or a placebo for 6 weeks. The primary endpoint was a significant reduction in IBS-symptom severity score (IBS-SSS). Secondary endpoints were changes in IBS symptoms, stool frequency, consistency, and quality of life. Results: The study group enrolled 50 patients, among which 22 participants from each group completed the study protocol. The glutamine group had significant changes in total IBS-severity score, dissatisfaction of bowel habit and interference with community function (58% reduction; P < 0.001, 57% reduction; P < 0.001, 51% reduction; P = 0.043, respectively). Improvement in IBS-severity score of more than 45% was observed in 22 of 25 participants (88%) in the glutamine group, while it was only 15 of 25 participants (60%) in the control group (p = 0.015). No serious adverse events were observed. Conclusions: Our findings indicated the superiority of adding glutamine supplementation to a low FODMAP diet in amelioration of IBS symptoms while confirming the beneficial effects of a low FODMAP diet in IBS management.